Specificity of Human Thymine DNA Glycosylase Depends on N-Glycosidic Bond Stability - Bennett, Matthew T. (2006)
Initiating the DNA base excision repair pathway, DNA glycosylases find and hydrolytically excise damaged bases from DNA. While some DNA glycosylases exhibit narrow specificity, others remove multiple forms of damage. Human thymine DNA glycosylase (hTDG) cleaves thymine from mutagenic G·T mispairs and recognizes many additional lesions, and has a strong preference for nucleobases paired with guanine rather than adenine. Yet, hTDG avoids cytosine, despite the million-fold excess of normal G·C pairs over G·T mispairs. The mechanism of this remarkable and essential specificity has remained obscure. Here, we examine the possibility that hTDG specificity depends on the stability of the scissile base-sugar bond by determining the maximal activity (k(max)) against a series of nucleobases with varying leaving group ability. We find that hTDG removes 5-fluorouracil 78-fold faster than uracil and 5-chlorouracil 572-fold faster than thymine, differences that can be attributed predominantly to leaving group ability. Moreover, hTDG readily excises cytosine analogues with improved leaving ability, including 5-fluorocytosine, 5-bromocytosine, and 5-hydroxycytosine, indicating that cytosine has access to the active site. A plot of log(k(max)) versus leaving group pK(a) reveals a Brønsted-type linear free energy relationship with a large negative slope of β(lg) = −1.6 ± 0.2, consistent with a highly dissociative reaction mechanism. Further, we find that the hydrophobic active site of hTDG contributes to its specificity by enhancing the inherent differences in substrate reactivity. Thus, hTDG specificity depends on N-glycosidic bond stability, and the discrimination against cytosine is due largely to its very poor leaving ability rather than its exclusion from the active site.